2009
DOI: 10.1073/pnas.0905343106
|View full text |Cite
|
Sign up to set email alerts
|

How oxygen attacks [FeFe] hydrogenases from photosynthetic organisms

Abstract: Green algae such as Chlamydomonas reinhardtii synthesize an [FeFe] hydrogenase that is highly active in hydrogen evolution. However, the extreme sensitivity of [FeFe] hydrogenases to oxygen presents a major challenge for exploiting these organisms to achieve sustainable photosynthetic hydrogen production. In this study, the mechanism of oxygen inactivation of the [FeFe] hydrogenase CrHydA1 from C. reinhardtii has been investigated. X-ray absorption spectroscopy shows that reaction with oxygen results in destr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

31
323
0
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 315 publications
(369 citation statements)
references
References 42 publications
31
323
0
3
Order By: Relevance
“…In the case of CaHydA, for which negligible inactivation occurs at high potential, it is clear that the oxidation current reaches an almost flat limiting value, consistent with H 2 oxidation becoming controlled by a chemical rather than an electrochemical step (under 100% H 2 the oxidation current is independent of rotation rate above 2,000 rpm and so is not controlled by mass transport of H 2 to the electrode). The [FeFe]-hydrogenase CrHydA1 consistently shows a small inflection in the catalytic current at potentials slightly above and below E 2H þ ∕H 2 (30). The H þ reduction activity of both [FeFe]-hydrogenases increases strongly as the electrode potential becomes more negative.…”
Section: Modelmentioning
confidence: 93%
“…In the case of CaHydA, for which negligible inactivation occurs at high potential, it is clear that the oxidation current reaches an almost flat limiting value, consistent with H 2 oxidation becoming controlled by a chemical rather than an electrochemical step (under 100% H 2 the oxidation current is independent of rotation rate above 2,000 rpm and so is not controlled by mass transport of H 2 to the electrode). The [FeFe]-hydrogenase CrHydA1 consistently shows a small inflection in the catalytic current at potentials slightly above and below E 2H þ ∕H 2 (30). The H þ reduction activity of both [FeFe]-hydrogenases increases strongly as the electrode potential becomes more negative.…”
Section: Modelmentioning
confidence: 93%
“…Relatively higher H 2 ase activity was observed under lower initial O 2 conditions (5-10%) compared with the higher O 2 environment (atmospheric O 2 ), but no apparent correlation was observed between the specific H 2 ase activity and the microalgal biomass amount as the activity significantly varied for similar biomass when the inorganic carbon concentration was fixed at 10% (Figs 1f and 4). H 2 ase is extremely sensitive to oxygen, and its activity is inhibited even on exposure to low concentrations of oxygen 19 . However, in the present study, H 2 ase activity at partial pressure of oxygen (5-21%) consistently indicated that the microalgae could perform hydrogen production and/or H 2 ase synthesis, even in 21% oxygen (Figs 2 and 4 and Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The enzymes themselves are extremely effective catalysts of the reduction of protons to dihydrogen in vivo but are not technologically viable for several reasons, not least their sensitivity to oxygen. 1 In recent years, it has been shown that many synthetic compounds based loosely on the active site structure of these enzymes also have the ability to produce hydrogen. [2][3][4][5][6][7][8][9] These iron-or nickel-based mimics are particularly attractive as they offer the possibility of replacing the platinum-based systems currently in technological use with more economically-viable materials.…”
Section: Supporting Information Placeholdermentioning
confidence: 99%